SEPARATE CLINICAL CASES WITH EFFICIENT CRT THERAPY - A. S. Postol; A. V. Ivanchenko; V. V. Lyashenko; A. B. Vygovsky; J. A. Shneider (Инновационная медицина Кубани)
We demonstrated findings regarding left ventricle electrode implantation with CRT, and suggested alternative implantation version, and performed analysis of therapy efficiency in cases with transseptal implantation technique.